Kecemasan Mahasiswa Sarjana Keperawatan Saat Menghadapi Ujian Osca Komprehensif Di Universitas Muhammadiyah Surakarta - Pusparatri, Edita; , Enita Dewi, S.Kep., Ns., MN (2016)
Objective Structured Clinical Assessment or OSCA is a comprehensive method used to evaluate the student health knowledge, attitudes, and skills in simulated clinical situations. Implementation OSCA generally causes anxiety in students, especially at the beginning of the semester students. This study aimed to determine anxiety Bachelor of Nursing students in the face of OSCA comprehensive exam at Universitas Muhammadiyah Surakarta. This research is a descriptive cross sectional study conducted on 33 students of the second semester and 35 students of the fourth semester at Universitas Muhammadiyah Surakarta with proportionate stratified random sampling technique. Collecting data using a questionnaire study were then analyzed using descriptive test. The results of this study are the demographic characteristics of the second and fourth semesters nursing undergraduate students at Universitas Muhammadiyah Surakarta mostly aged 19-20 years old and female. Based on responses to questionnaires SAS scores of affective responses and somatic symptoms showed that second and fourth semesters, students have a tendency to anxiety responses have maladaptive coping in the exam OSCA. The conclusion of this study is the nursing undergraduate students in the face of a comprehensive test of OSCA has affective response and maladaptive somatic symptoms.